The Effect of Prenatal Yoga on Back Pain in Pregnant Women - Nareswari Nugraha; Candra Dewi Nataningtyas; Herdian (Health and Technology Journal (HTechJ), 2025)
Hormonal changes during pregnancy alter the soft tissue that supports and connects the muscles, thereby reducing muscle flexibility and resulting in pregnant women's back pain. The purpose of this research is to determine whether prenatal yoga helps pregnant women with back discomfort. A pre-experimental research design was used. Non-probability sampling was conducted using a one-group pre-test-post-test design. We used the accidental sampling method to select 10 participants for the sample at random. A pregnant woman who happened to meet a researcher could be used as a sample when viewed as a suitable respondent. Data collection was done with observation sheets using the Numeric Rating Scale pain scale. According to the Wilcoxon test results, H0 is rejected and H1 is obtained, the ρ value is equal to 0.001, and the α value is less than 0.05. A 1.9% decrease is indicated by the average difference of 6.40 ± 4.50 between the pretest and posttest. The findings of this study indicate that expectant mothers' discomfort can be lessened by using prenatal yoga. Prenatal yoga may help pregnant women with back pain, according to one study. Prenatal yoga is intended to be used in conjunction with other therapies as a supplemental treatment to help pregnant women with their back pain.